BIRTH WEIGHT AND BIRTH LENGTH AFFECTING STUNTING INCIDENT IN TODDLER - Augustien Julia Sawitri; Bambang Purwanto; Irwanto - (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: East Java is one of the regions in Indonesia that has received more attention regarding stunting because the incidence has around 36%. Stunting is a phenomenon of malnutrition that occurs in children where there are growing problems related to the length or height of the child. The history of choric energy deficiency in the mother during pregnancy, birth weight, and birth length is closely related to the incidence of stunting. The incidence of stunting at the Puskesmas Tambak Wedi Surabaya in 2018 was 18.9%. This data has increased from 2017 to 2.7%. Therefore, this study aims to determine the relationship between birth weight and birth length with the incidence of stunting under five at Puskesmas Tambak Wedi Surabaya. Methods: This study used observational analytic with a cross-sectional approach. The sample used was 30 toddlers with a simple random sampling technique. Stunting in toddlers is included in the dependent variable, while birth weight and birth length are included in the independent variables. Spearman's test was used to analyze the data in this study. Results: This study shows that there is a relationship between birth weight and the incidence of stunting in children under five who obtained a correlation coefficient value of 0.450 with a p-value of 0.012 with sufficient strength and there was a relationship between birth length and the incidence of stunting under-five children who obtained a correlation coefficient value of 0.463 with a p-value of 0.010 with sufficient relationship strength. Conclusion: Birth weight and birth length are associated with the incidence of stunting under five. Mothers need to follow the advice of health workers in maintaining nutrition during preconception, antenatal, natal, and post-natal periods with the help of the husband and family.